Analisis Mutu dan Kualitas Input-Proses-Output Pendidikan di MAN 1 Tulang Bawang Barat - Aulia Diana Devi (STAI Terpadu Yogyakarta, 2021)
A good education is a quality education. This research aims to analyze the quality and quality of inputs, processes, and educational outputs in MAN 1 Tulang Bawang Barat Lampung. The method used is descriptive analysis using a qualitative approach. This research conducts data collection techniques by means of observation, interview, literature studies, and internet media. The study used primary data sources obtained through interviews and secondary data sources obtained through online media. The results show that (1) In order to achieve vision and mission, the head of the madrasah must always be able to communicate with the madrassa stakeholders. In addition, this vision and mission is also supported by a wide range of strategic flagship programs both academic and non-academic activities, (2) MAN 1 Tulang Bawang Barat has good achievements in academic and non-academic fields, (3) Has facilities and infrastructure above minimum standards, (4) Man 1 Tulang Bawang Barat graduates are able to compete in continuing the best level of education.